542 Objective Sleep Duration, Sleep Timing and Completion of In Vitro Fertilization Cycles; a Prospective Cohort Study. (3rd May 2021) - Pimolsri, Chawanont; Lyu, Xiru; Goldstein, Cathy; Fortin, Chelsea; Mumford, Sunni; Smith, Yolanda; Lanham, Michael; O'Brien, Louise; Dunietz, Galit Levi
Abstract: Introduction: Sleep duration and circadian misalignment have been linked to fertility and fecundability. However, sleep in women undergoing IVF has rarely been examined. This study investigated the role of sleep duration and timing with completion of an IVF cycle. Methods: Prospective study of women undergoing IVF at a tertiary medical center between 2015 and 2017. Sleep was assessed by wrist-worn actigraphy 1–2 weeks prior to the initiation of their IVF cycle. Reproductive profile, IVF cycle details, demographic and health information were obtained from medical charts. Sleep duration, midpoint and bedtime were examined in relation to IVF cycle completion using logistic regression models, adjusted for age and anti-Müllerian hormone levels. A sub-analysis excluded women who worked non-day shifts to control for circadian misalignment. Results: A total of 48 women were studied. Median age was 33y (range 25–42), with 29% of women older than 35 years. Ten women had an IVF cycle cancellation prior to embryo transfer. These women had shorter sleep duration, more nocturnal awakenings, lower sleep efficiency, and later sleep timing in comparison to those who completed their cycle. Twenty-minute increases in sleep duration were associated with lower odds of an uncompleted IVF cycle (OR = 0.88; 95% CI 0.78, 1.00). Women with later sleep midpoints and later bedtime had higher odds of an uncompleted cycle relative to those with earlier midpoints and earlier bedtime; OR=1.24; 95% CI 1.09, 1.40 and OR=1.33; 95% CI 1.17, 1.53 respectively, per 20-minute increments. These results were independent of age, levels of anti-Müllerian hormone, or sleep duration, and remained unchanged after exclusion of shift-working women. Conclusion: This study demonstrated the influence of sleep duration and sleep timing on the odds of an uncompleted IVF cycle prior to embryo transfer. Sleep is a modifiable behavior that may contribute to IVF cycle success. Support (if any):